2005
DOI: 10.1373/clinchem.2005.056838
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Time of Last Cannabis Use from Plasma Δ9-Tetrahydrocannabinol and 11-nor-9-Carboxy-Δ9-Tetrahydrocannabinol Concentrations

Abstract: Background: Knowing the time cannabis was last used is important for determining impairment in accident investigations and clinical evaluations. Two models for predicting time of last cannabis use from single plasma cannabinoid concentrations-model I, using ⌬ 9 -tetrahydrocannabinol (THC), and model II, using the concentration ratio of 11-nor-9-carboxy-THC (THCCOOH) to THC-were developed and validated from controlled drug administration studies. Objectives of the current study were to extend the validation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 28 publications
3
52
0
3
Order By: Relevance
“…Cannabis is first converted to an active metabolite, 11-hydroxy-delta-9-tetrahydrocannabinol (11-OH-THC), and then to its inactive form, 11-nor-9-carboxy-delta-9-tetrahydrocannabinol (THC-COOH) by the cytochrome family of enzymes [73, 74]. We are only aware of one study that found that CYP2C9*3 carriers were more likely to have higher concentrations of THC and, correspondingly, lower concentrations of THC-COOH and show greater sedation upon oral THC administration [75].…”
Section: Gene Finding Effortsmentioning
confidence: 99%
“…Cannabis is first converted to an active metabolite, 11-hydroxy-delta-9-tetrahydrocannabinol (11-OH-THC), and then to its inactive form, 11-nor-9-carboxy-delta-9-tetrahydrocannabinol (THC-COOH) by the cytochrome family of enzymes [73, 74]. We are only aware of one study that found that CYP2C9*3 carriers were more likely to have higher concentrations of THC and, correspondingly, lower concentrations of THC-COOH and show greater sedation upon oral THC administration [75].…”
Section: Gene Finding Effortsmentioning
confidence: 99%
“…Model I determines time estimates from plasma THC concentrations and Model II from plasma concentration ratios of THCCOOH/THC. where T represents the elapsed time in hours between commencing smoking cannabis and blood collection and CI represents the 95% confidence interval for the estimate of T. Validation of these predictive models including estimation of the time of use after multiple doses of THC and at low THC concentrations (0.5-2 ng/mL) showed that Model I was less accurate with primary overestimates that benefit the accused (Huestis et al 2005). Model II was more accurate and had no underestimates for multiple doses.…”
Section: Distributionmentioning
confidence: 99%
“…Des modèles mathématiques ont été développés pour estimer le moment de la prise de cannabis connaissant les concentrations plasmatiques du THC et du THCCOOH [72].…”
Section: Pharmacocinétiqueunclassified
“…Ces résultats indiquent que l'analyse de la salive est une bonne stratégie pour détecter les conducteurs de véhicule conduisant sous l'influence du cannabis, mais qu'un test simple, rapide, performant et bon marché, praticable au bord de la route, n'est à notre avis pas encore disponible en 2008. Le dosage du THC dans le sang, le plasma ou le sérum permet d'évaluer l'effet de la prise de cannabis sur le comportement ou les performances et d'évaluer le moment de la prise au moyen de différents modèles pharmacocinétiques [72]. Lors de consommations régulières de cannabis, les cannabinoïdes se trouvent piégés dans la matrice du cheveu.…”
Section: Dépistage De Consommationunclassified